2017
DOI: 10.5935/0004-2749.20170050
|View full text |Cite
|
Sign up to set email alerts
|

Corneal properties and glaucoma: a review of the literature and meta-analysis

Abstract: Corneal properties appear to differ between glaucoma patients and healthy controls. Our results emphasize the importance of corneal biomechanical properties in IOP interpretation and should support further studies on the influence of CH and CCT in glaucoma screening and diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…As shown in other publications, in our study, both CH and CRF values were lower in POAG patients than in OH patients and in NE [ 10 , 24 , 25 , 30 , 31 , 33 , 36 40 ], and a study that included both eyes of POAG patients revealed that the most affected eye had a lower CH compared to the other eye [ 16 ]. Moreover, studies revealed that a high CH has a protective role in OH patients [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in other publications, in our study, both CH and CRF values were lower in POAG patients than in OH patients and in NE [ 10 , 24 , 25 , 30 , 31 , 33 , 36 40 ], and a study that included both eyes of POAG patients revealed that the most affected eye had a lower CH compared to the other eye [ 16 ]. Moreover, studies revealed that a high CH has a protective role in OH patients [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our study revealed that means of GCC thickness were higher in NE than in OH eyes and higher than in POAG patients. Other studies also proved that in glaucoma patients, means of GCC correspond to means of pRNFL and are lower than in normal individuals [ 10 , 18 , 38 , 41 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, important correlations between corneal pachymetry and glaucoma have emerged unequivocally, due to the diffusion of refractive surgery and the related pre-op tests. Considering that the CCT in normal conditions is just over half a millimeter (540 ± micron), patients with thin cornea have a higher risk of development and progression of glaucomatous damage, while those with thick cornea are more protected from glaucomatous risk ( Figure 6) (Gaspar et al, 2017;Belovay and Goldberg, 2018). However, it is important to remember that measurement of IOP by standard techniques is lower than the real value in patients with thin cornea and higher in those with thick cornea.…”
Section: Glaucoma Diagnosismentioning
confidence: 99%
“…ст., 95 % ДИ [-1,68, -1,41], p < 0,0001) отмечено в результате обобщенного анализа R. Gaspar и соавт. [28]. В этом же исследовании ЦТР была значительно ниже в группе глаукомы, чем в контрольной группе (MD = -8,49 мкм, 95 % ДИ [-11,36, -5,62], p < 0,001).…”
unclassified